Penerapan Algoritma Gost Dan Mode Output Feedback Untuk Tingkat Keamanan Citra Digital - Sri Wahyuni; Surya Darma Nasution; Taronisokhi Zebua (Journal of Informatics Management and Information Technology, 2021)
Digital images that are private and confidential are very vulnerable to wiretapping by irresponsible parties. Especially if it is distributed over the internet such as chat-based applications, WhatsApp and e-mail media. The image that is sent is sometimes an image that is confidential and must be protected. In order to maintain the security of digital images, cryptographic techniques can be used. Cryptographic techniques can secure digital images by changing the pixel values ??of the digital image so that it produces a different pixel value from the original image to be secured. In this study, the algorithm used is the GOST algorithm by adding the OFB technique to optimize the GOST key, and the encryption results can be sent via an application that will be designed with a client-server model. Creating a client-server-based encryption and decryption software application, aimed at transferring digital data in the form of a plain image that has been encrypted using the GOST algorithm, and can be distributed locally using an IP address connected to the same network on the sending and receiving computers (client-server)